ASPEK HUKUM PASAR MODAL SYARIAH DI INDONESIA - Redi Hadiyanto; Lina Pusvisasari (Prodi Hukum Keluarga Islam (Ahwal Asy-Syakhsiyyah) Fakultas Syariah Unisba, 2021)
Along with the development of the times in the capital market experienced several developments such as the existence of the Islamic capital market. Indonesia is one of the countries that has developed a sharia capital market, therefore the role of the government and MUI should be to make legal regulations that regulate and become the basis for capital market activities so that they are in line with sharia principles so that as Indonesian Muslims it is important to know and apply them. This study aims to analyze the legal aspects of the Islamic capital market in Indonesia. The method used in this study is a normative juridical research method with a qualitative approach, analyzing the laws and concepts of the Islamic capital market in Islamic law. The results of the study show that in Indonesia the Islamic capital market was officially launched on March 14, 2003 along with the signing of the MoU and BAPEPAM-LK with the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). In 2003, the DSN-MUI issued a fatwa regarding the permissibility of transactions in the capital market as long as the mechanism and object did not conflict with sharia principles. The fatwas issued by the DSN relate to the general provisions of the sharia capital market, its principles, issuers issuing sharia securities, criteria and types of sharia securities, prohibited transactions and determination of share prices.Keywords: Sharia Capital Market, Sharia Capital Market Law